High-intensity circuit training improves cognitive performance independent of changes in sBDNF levels in active college students - Jiménez Maldonado, Alberto (2025)
High-intensity circuit training (HICT) is an exercise modality converging aerobic and resistance exercises executed at high-intensity interspersed by recovery periods. During the HICT, the participants use their body weight as resistance. The impact of HICT on metabolic and cardiovascular markers has been reported, the effect of HICT on brain function remains unknown. The current study was focus to evaluate the impact of 24 HICT sessions on the serum BDNF (sBDNF) levels and cognition skills in young adults. Fifteen college students (22.1 ± 5.3 yr.) were randomly assigned to a control (CTRL) (n = 7) or a HICT (n = 8) group. The CTRL group continued their daily activities without restricting their physical activities, the HICT group carried out 24 HICT sessions. The sBDNF levels of all participants pre- and post-HICT intervention were determined by ELISA method. Visual memory, verbal memory, semantic verbal fluency, and attention were evaluated with specific neuropsychological tests. The heart rate variability (HRV) was recorded at rest in the supine position (5 min) for both groups at the beginning of the HICT program and 24 h after the intervention. The sBDNF levels increased in both groups at the end of the study (p < 0.0001). Visual memory (delayed recall) and long-term verbal memory significantly improved after HICT (p < 0.01). The HRV was unchanged by HICT. In conclusion, HICT might be a feasible method to improve cognition abilities in active young adults, and it is becoming a good option for college students since the intervention did not induce physiological stress in the participants.